ALGORITMA MODEL PENENTUAN LOKASI FASILITAS TUNGGAL DENGAN PROGRAM DINAMIK - Firmansyah Firmansyah; Rima Aprilia (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2018)
Facility plays an important role of the real world, the facility is no longer a secondary requirement but becomes a primary need. Provision of facilities from any company requires a competitive location, so that the facilities provided can be useful for others. Dynamic Programming was once used to determine the best opening schedule of Subset as an "optimal" location and relocation strategy for planning. So in this research done determination of location of facility and its relocation with dynamic programming so hopefully can use optimal budget with optimal time.Keywords: Facility Location, Dynamic Programming